Da liberdade humana às faces do mal na hermenêutica ricoeuriana - Pessoa, Hubert Milanes (2014)
The Paul Ricoeur‟s hermeneutics aims the comprehension of man through the language as from his own historical context, his own tradition, in other words, the knowledge of this man as a wight that constitutes himself and the sense of his own existence. From Ricoeur‟s hermeneutics it will draw a possible dialogue with this subject that, possessor of his liberty, is responsible about his own actions, whether good, whether bad. Ricoeur presents an internalized language of confession of the penitent as been a word that, repeatedly and continuously, will induce a search for a badly philosophical and ontological interpretation. We will reflect about primary bad signs, put differently, the macula, the sin and the guiltiness. Avoid the evil practice is an exhaustive theme present in the French philosopher‟s works, being this an attempt of avoid a big ethic challenge to the subject.